0 рейтинг
21 видели

1) упростите выражение 2,9 - ( x - 6,7 ) =

c - ( a+ c ) =

решите уравнение 8,4 - ( x - 7,2 ) = 8,6

-1,3 + ( x - 4,8 ) = -7,1

от (26 баллов) в разделе Математика | 21 видели

2 Ответов и Решений

0 рейтинг
Правильный ответ

1) упростите выражение 2,9 - ( x - 6,7 ) =2,9-х+6,7=9,6+х

 

c - ( a+ c ) =с-а-с=-а

 

решите уравнение 8,4 - (  x - 7,2 ) = 8,6

                             8,4-х+7,2=8,6

                             15,6-х=8,6

                             х=15,6-8,6

                              х=7

 

-1,3 + ( x - 4,8 ) = -7,1

-1,3+х-4,8=-7,1

  -6,1+х=-7,1

   х=-7,1+6,1

    х=-1

 
от (106k баллов)
0 рейтинг

8.4-x+7.2=8.6

-x=8.6-7.2-8.4

-x=-7

x=7

 

-1.3+x-4.8=-7.1

x=-7.1+4.8+1.3

x=-1

 

c-a-c=-a

 

2.9-x+6.7=-x+9.6

от (68 баллов)
10,984,878 заданий
13,471,016 решений
8,518,553 комментариев
4,909,216 пользователей